2016
DOI: 10.1007/s00213-016-4390-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of methylphenidate and propranolol on the interplay between induced-anxiety and working memory

Abstract: Rationale Research documents a reciprocal impact of anxiety on working memory (WM), although its strength and direction depend on factors like task difficulty. A better understanding of these factors may generate insights into cognitive mechanisms of action involved in anxiety, culminating into treatment implications. By blocking the physiological effects of anxiety, propranolol might also block anxiety interference on WM. Conversely, by improving task-directed attention, methylphenidate might reduce anxiety, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 41 publications
(64 reference statements)
0
26
1
1
Order By: Relevance
“…Finally, this study design did not include a noactivity control. For example, contrary to expectations (Ernst et al, 2016; Shackman et al, 2006; Vytal et al, 2012), the threat did not impair WM (accuracy or RT) in the control-activity. This result may be due to effects of light intensity activity, but without a no-activity control, this hypothesis cannot be tested.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…Finally, this study design did not include a noactivity control. For example, contrary to expectations (Ernst et al, 2016; Shackman et al, 2006; Vytal et al, 2012), the threat did not impair WM (accuracy or RT) in the control-activity. This result may be due to effects of light intensity activity, but without a no-activity control, this hypothesis cannot be tested.…”
Section: Discussioncontrasting
confidence: 97%
“…Prior data from our lab (Ernst et al, 2016; Vytal et al, 2012) indicated an expected moderate effect size for startle potentiation (Cohen’s d = 0.45). A priori calculations indicated that testing of 36 participants at an alpha of 0.05 would provide the power of 0.95 to detect a significant 2 (Activity) × 2 (Load) interaction on startle.…”
Section: Methodsmentioning
confidence: 81%
See 2 more Smart Citations
“…This suggests that threat impairs WM manipulation processes in the dlPFC. Indeed, there have been a number of studies investigating the effect of threat on WM, primarily using the n -back WM task ( Vytal et al , 2012 2013 ; Clarke and Johnstone, 2013 ; Patel et al , 2016 ; Ernst et al , 2016 ). The major findings from these studies are that (i) threat reduces accuracy, especially on low-load WM trials ( Vytal et al , 2012 2013 ; Patel et al , 2016 ) and (ii) threat reduces overall dlPFC processing ( Clarke and Johnstone, 2013 ).…”
Section: Discussionmentioning
confidence: 99%